Green synthesis and characterization of zinc chitosan nanoparticles with their anti-bacterial study against rice pathogen Xanthomonas oryzae pv. oryzae - Lutfur Rahman; Rumana Akter; Md. Omar Kayess; Rakibul Hasan; A. K. M. Sahfiqul Islam; Sheikh Arafat Islam Nihad; A. K. M. Mohiuddin; A. L. Nayeem; Mohammad Abdul Latif (PLoS ONE, 2026)
Bacterial leaf blight (BLB) of rice is caused by the bacterium Xanthomonas oryzae pv. oryzae ( Xo o) and leads to significant yield loss. The overuse of antibacterial chemicals casuse environmental toxicity, high cost, and low biosafety generating interest in eco-friendly alternatives.This study evaluated the antibacterial efficacy of biosynthesized zinc–chitosan nanoparticles (ZnChNPs) against Xanthomonas oryzae pv. oryzae ( Xoo ). Successful synthesis was confirmed by UV–visible spectroscopy with a characteristic absorption peak at 356 nm. Comprehensive physicochemical characterization using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and field emission scanning electron microscopy (FESEM) revealed ZnChNPs with diverse polymorphic morphologies, while energy dispersive spectroscopy (EDS) confirmed zinc, oxygen, and carbon as the major elemental components. Fourier transform infrared spectroscopy (FTIR) analysis identified key functional groups associated with nanoparticle formation and stabilization, and X-ray diffraction (XRD) patterns verified a crystalline hexagonal wurtzite structure. Dynamic light scattering (DLS) measurements showed a mean hydrodynamic diameter of 256.2 nm, and a zeta potential of −25.1 mV indicated good colloidal stability of the formulation. In vitro , ZnChNPs:dH₂O at 8:2 and 10:0 ratios showed inhibition zones of 22.75 mm and 24.84 mm, respectively. In net house conditions, treatments reduced BLB lesion lengths by 36%–73.54% at 14 days and 34.98%–63.66% at 21 days. The Bismerthiazol (0.15%) + ZnChNP:dH₂O (8:2) treatment reduced lesions by 68.28% and 55.48% at 14 and 21 days, respectively. Field trial results showed 66.14% and 61.27% reductions at 14 and 21 days. These findings suggest ZnChNPs can be used as a sustainable strategy for controlling BLB in rice in an effective manner.